Development of agro-tourism as additional services in rural areas Brčko District BIH - Maksimović, Aleksandar; Grgić, Zoran; Bicanić, Danijela (Economics of Agriculture, 2010)
Rural areas in the Brcko District provides current characteristics and rural areas may be attractive to undertake tourism activities. They presented folk costumes and folk dances, customs, religious buildings, cultural and historical monuments, gastronomy, hospitality people, etc.. Rich with natural potential and traditional values conducive to tourism as one of the possible conditions for the development of a somewhat neglected rural areas Brcko district. Area of Brcko District has the potential application of agrotourism as a complementary activity of family farms, as a family business in most places, apart from regular farm duties; faithfully maintain the tradition, gastronomy and interesting customs that must be used to promote tourism potential. Therefore the main objective is to present tourism as a supplementary activity in the rural area of Brcko District as a solid development opportunity that will simultaneously help develop rural areas and create new jobs, which is essential in overcoming the ever-present economic crisis.